TALENT-BASED EDUCATION IN INDONESIAN PRIMARY SCHOOLS: INTEGRATING KI HADJAR DEWANTARA"™S PHILOSOPHY FOR INCLUSIVE LEARNING - Taufikin, Taufikin; Nurhayati, Sri (Jurnal Visi Ilmu Pendidikan, 2026)
Talent-based education has gained increasing attention in modern educational systems due to its potential to develop student's skills and interests optimally. This study aims to analyze the implementation of talent-based education in elementary schools from the perspective of Ki Hadjar Dewantara and to identify challenges and strategies to enhance its effectiveness. A qualitative research method was employed with a case study approach involving three elementary schools that have implemented talent-based education programs. Data were collected through in-depth interviews with school principals, teachers, students, and parents, as well as observations and document analysis. Thematic analysis was used to identify patterns and key challenges in the implementation of talent-based education. The findings indicate that talent-based education positively impacts students' learning motivation, self-confidence, and social skills. However, several key challenges were identified, including limited facilities, insufficient teacher training, and suboptimal integration with the national curriculum. This study also reveals that Ki Hadjar Dewantara"™s philosophy offers a more inclusive approach than the selection-based talent education models applied in various countries. Therefore, strengthening educational policies, institutional support, and continuous professional development for educators are essential factors in improving the effectiveness of these programs. This research contributes to the literature on talent-based education by highlighting a more flexible and inclusive culturally rooted approach. The findings are expected to serve as a foundation for policymakers and educators in designing an education system that is more adaptive and focused on optimizing students' potential.Keywords: , , , , .